In vitro mapping of 1H ultrashort T2* and T2 of porcine menisci. (18th March 2013) - Kirsch, S.; Kreinest, M.; Reisig, G.; Schwarz, M. L. R.; Ströbel, P.; Schad, L. R.
<x xml:space="preserve">Abstract</x> In this study, mapping of ultrashort T2 and T2* of acutely isolated porcine menisci at B0 = 9.4 T was investigated. Maps of T2 were measured from a slice through the pars intermedia with a spin echo‐prepared two‐dimensional ultrashort‐TE T2 mapping technique published previously. T2* mapping was performed by two‐dimensional ultrashort‐TE MRI with variable acquisition delay. The measured signal decays were fitted by monoexponential, biexponential and Gaussian‐exponential fitting functions. The occurrence of Gaussian‐like signal decays is outlined theoretically. The quality of the curve fits was visualized by mapping the value δ = abs(1 – χ2red). For T2* mapping, the Gaussian‐exponential fit showed the best performance, whereas the monoexponential and biexponential fits showed regionally high values of δ (δ > 20). Interpretation of the Gaussian‐exponential parameter maps was found to be difficult, because a Gaussian signal component can be related to mesoscopic (collagen texture) or macroscopic (slice profile, shim, sample geometry) magnetic field inhomogeneities and/or residual 1H dipole–dipole couplings. It seems likely that an interplay of these effects yielded the observed signal decays. Modulation of the T2* signal decay caused by chemical shift was observed and addressed to fat protons by means of histology. In the T2 measurements, no modulation of the signal decay was observed and the biexponential and Gaussian‐exponential fits showed the best performance with comparable values of δ. Our results suggest that T2 mapping provides the more robust method for the characterization of meniscal tissue by means of MRI relaxometry. However, mapping of ultrashort T2, as performed in this study, is time consuming and provides less signal‐to‐noise ratio per time than the mapping of T2*. If T2* mapping is used, pixel‐wise monitoring of the fitting quality based on reduced χ2 should be employed and great care should be taken when interpreting the parameter maps of the fits. Copyright © 2013 John Wiley & Sons, Ltd.